Lithium battery and preparation method thereof

By arranging the solid electrolyte layers of the positive and negative electrodes in a lithium battery relative to each other, a lithium ion diffusion channel is constructed that runs through the positive and negative electrodes, which solves the rate performance and safety problems of the lithium battery and achieves efficient lithium ion migration and improved safety performance.

CN120809914APending Publication Date: 2025-10-17JIANGSU ZENIO NEW ENERGY BATTERY TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510948988.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-07-10
Publication Date
2025-10-17

AI Technical Summary

Technical Problem

The rate performance and safety of lithium batteries are limited by the porosity of the diaphragm and the ionic conductivity of the liquid electrolyte. The diaphragm of traditional liquid lithium batteries affects the migration of lithium ions, and the low ionic conductivity of solid-state lithium batteries limits performance improvements.

Method used

The solid electrolyte layers of the positive electrode and the negative electrode are arranged relative to each other. The positive electrode solid electrolyte layer includes LixAl2O3, and the negative electrode solid electrolyte layer includes an oxide that reacts with lithium metal to generate a solid electrolyte with similar properties, constructing a lithium ion diffusion channel running through the positive and negative electrodes, and combining a polymer layer and an electrolyte to improve the interface contact.

Benefits of technology

Improve the rate performance and cycle performance of lithium batteries, reduce the risk of electrolyte leakage, and improve safety performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120809914A_ABST
    Figure CN120809914A_ABST
Patent Text Reader

Abstract

The invention relates to a lithium battery and a preparation method thereof, the lithium battery comprises a shell and an electrode assembly located in the shell, and the electrode assembly comprises a positive plate and a negative plate; the positive plate comprises a positive current collector, a positive active material layer arranged on the surface of the positive current collector, and a positive solid electrolyte layer arranged on the surface of one side, far away from the positive current collector, of the positive active material layer; the positive electrode solid electrolyte layer comprises LixAl2O3 (x is more than 0 and less than or equal to 4); the negative plate comprises a negative current collector, a negative active material layer arranged on the surface of the negative current collector, and a negative solid electrolyte layer arranged on the surface of one side, far away from the negative current collector, of the negative active material layer; the negative electrode solid-state electrolyte layer comprises a negative electrode solid-state electrolyte and an oxide, and the oxide can react with lithium metal to generate a solid-state electrolyte; and the positive electrode solid electrolyte layer and the negative electrode solid electrolyte layer are oppositely arranged. Therefore, the rate capability and the cycle performance of the lithium battery can be effectively improved.
Need to check novelty before this filing date? Find Prior Art

Description

TECHNICAL FIELD

[0001] The present application relates to the technical field of batteries, in particular to a lithium battery and a preparation method thereof. BACKGROUND

[0002] Lithium batteries have been widely used in the fields of portable electronic products, electric vehicles and energy storage devices. However, the rate performance bottleneck of lithium batteries significantly limits their further expansion in high-power application fields.

[0003] In a conventional liquid lithium battery, the separator, as a key component for isolating the positive electrode sheet and the negative electrode sheet, can insulate electrons and conduct ions. If the porosity of the separator is too low, it will increase the ion migration resistance, resulting in an increase in the internal resistance of the battery, thereby affecting the rate performance of the battery. In order to improve the rate performance of the battery, a separator with high porosity is usually used. However, if the porosity of the separator is too high, the mechanical strength of the separator will be reduced, which will threaten the safety of the battery.

[0004] Solid-state lithium batteries use solid-state electrolytes instead of conventional liquid electrolytes, do not need to set up separators, can avoid the influence of the porosity of the separator on ion migration, and have the advantage of high safety. However, the ionic conductivity of the solid-state electrolyte is lower than that of the liquid electrolyte, which restricts the improvement of the rate performance of the solid-state lithium battery. SUMMARY

[0005] Therefore, the present application provides a lithium battery and a preparation method thereof to solve at least one problem in the background art.

[0006] In a first aspect, the present application provides a lithium battery, comprising a shell and an electrode assembly located in the shell, wherein the electrode assembly comprises a positive electrode sheet and a negative electrode sheet.

[0007] The positive electrode sheet comprises a positive electrode current collector, a positive electrode active material layer arranged on the surface of the positive electrode current collector, and a positive electrode solid-state electrolyte layer arranged on the surface of the positive electrode active material layer away from the positive electrode current collector; the positive electrode solid-state electrolyte layer comprises Li x Al2O3(0 < x < 4);

[0008] The negative electrode sheet comprises a negative electrode current collector, a negative electrode active material layer arranged on the surface of the negative electrode current collector, and a negative electrode solid-state electrolyte layer arranged on the surface of the negative electrode active material layer away from the negative electrode current collector; the negative electrode solid-state electrolyte layer comprises a negative electrode solid-state electrolyte and an oxide, and the oxide can react with lithium metal to generate a solid-state electrolyte;

[0009] The positive electrode solid-state electrolyte layer and the negative electrode solid-state electrolyte layer are arranged opposite to each other.

[0010] In combination with the first aspect of the present application, in an optional implementation, the negative electrode sheet further comprises a polymer layer located on a side surface of the negative electrode solid electrolyte layer away from the negative electrode active material layer; optionally, the polymer layer comprises at least one of trimethylene carbonate, polymethyl methacrylate, and polyvinylidene fluoride; optionally, the thickness of the polymer layer is 3 μm to 8 μm.

[0011] In combination with the first aspect of the present application, in an optional implementation, the positive electrode sheet satisfies at least one of the following characteristics:

[0012] (1) the positive electrode solid electrolyte layer further comprises a NASICON-type solid electrolyte and / or a perovskite-type solid electrolyte; optionally, the mass ratio of the NASICON-type solid electrolyte and / or the perovskite-type solid electrolyte to the Li x Al2O3 is (4:1) to (3:2);

[0013] (2) the positive electrode active material layer comprises a positive electrode active material, and the positive electrode active material comprises at least one of ternary nickel-cobalt-manganese, ternary nickel-cobalt-aluminum, lithium iron phosphate, lithium cobaltate, lithium-rich manganese-based, and lithium manganate;

[0014] (3) the thickness of the positive electrode solid electrolyte layer is 5 μm to 15 μm;

[0015] (4) the thickness of the positive electrode active material layer is 80 μm to 250 μm.

[0016] In combination with the first aspect of the present application, in an optional implementation, the negative electrode sheet satisfies at least one of the following characteristics:

[0017] (1) the negative electrode solid electrolyte comprises a garnet-type solid electrolyte;

[0018] (2) the oxide comprises at least one of Al2O3, SnO2, SiO2, TiO2, and ZrO2;

[0019] (3) the mass ratio of the negative electrode solid electrolyte to the oxide is (1:4) to (2:3);

[0020] (4) the negative electrode active material layer comprises a negative electrode active material, and the negative electrode active material comprises at least one of graphite, silicon-oxygen material, silicon-carbon material, and lithium metal;

[0021] (5) the thickness of the negative electrode solid electrolyte layer is 5 μm to 15 μm;

[0022] (6) the thickness of the negative electrode active material layer is 70 μm to 200 μm;

[0023] (7) the reduction potential of the negative solid electrolyte is less than the reduction potential of the positive solid electrolyte layer.

[0024] In combination with the first aspect of the present application, in an optional implementation, the lithium battery further comprises an electrolyte, and the electrolyte comprises a lithium salt; optionally, the lithium salt comprises at least one of LiPF6, LiClO4, LiBF4, LiFSI and LiTFSI.

[0025] In the second aspect, the embodiments of the present application provide a preparation method of a lithium battery, and the method comprises the following steps:

[0026] forming, on the surface of the positive current collector, a positive active material layer and a positive solid electrolyte layer in sequence, wherein the positive solid electrolyte layer comprises Li x Al2O3(0<x≤4), to obtain a positive electrode sheet;

[0027] forming, on the surface of the negative current collector, a negative active material layer and a negative solid electrolyte layer in sequence, wherein the negative solid electrolyte layer comprises a negative solid electrolyte and an oxide, and the oxide can react with lithium metal to generate a solid electrolyte, to obtain a negative electrode sheet;

[0028] assembling the positive electrode sheet and the negative electrode sheet to obtain an electrode assembly; wherein the positive solid electrolyte layer and the negative solid electrolyte layer are arranged oppositely;

[0029] placing the electrode assembly in a shell to obtain the lithium battery.

[0030] In combination with the second aspect of the present application, in an optional implementation, the preparation of the negative electrode sheet further comprises forming a polymer layer on the surface of the negative solid electrolyte layer away from the negative active material layer; optionally, the thickness of the polymer layer is 3 μm to 8 μm; optionally, the formation of the polymer layer comprises:

[0031] dissolving a polymer in a solvent to form a mixed solution, ball-milling the mixed solution, and then coating the ball-milled mixed solution on the surface of a base film to form a polymer layer after drying; the polymer comprises at least one of trimethylene carbonate, polymethyl methacrylate and polyvinylidene fluoride;

[0032] transferring the polymer layer to the surface of the negative solid electrolyte layer away from the negative active material layer.

[0033] In combination with the second aspect of the present application, in an optional implementation, the preparation of the positive electrode sheet satisfies at least one of the following characteristics:

[0034] (1) the positive electrode solid electrolyte layer further comprises a NASICON type solid electrolyte and / or a perovskite type solid electrolyte; optionally, a mass ratio of the NASICON type solid electrolyte and / or the perovskite type solid electrolyte to the Li x a mass ratio of the Al2O3 to the Li

[0035] (2) the positive electrode active material layer comprises a positive electrode active material, and the positive electrode active material comprises at least one of a ternary nickel-cobalt-manganese, a ternary nickel-cobalt-aluminum, a lithium iron phosphate, a lithium cobaltate, a lithium-rich manganese-based, and a lithium manganate;

[0036] (3) a thickness of the positive electrode solid electrolyte layer is 5 μm to 15 μm;

[0037] (4) a thickness of the positive electrode active material layer is 80 μm to 250 μm.

[0038] In combination with the second aspect of the present application, in an optional implementation, the negative electrode sheet is prepared to meet at least one of the following characteristics:

[0039] (1) the negative electrode solid electrolyte comprises a garnet type solid electrolyte;

[0040] (2) the oxide comprises at least one of Al2O3, SnO2, SiO2, TiO2, and ZrO2;

[0041] (3) a mass ratio of the negative electrode solid electrolyte to the oxide is (1:4) to (2:3);

[0042] (4) the negative electrode active material layer comprises a negative electrode active material, and the negative electrode active material comprises at least one of graphite, silicon-oxygen material, silicon-carbon material, and lithium metal;

[0043] (5) a thickness of the negative electrode solid electrolyte layer is 5 μm to 15 μm;

[0044] (6) a thickness of the negative electrode active material layer is 70 μm to 200 μm;

[0045] (7) a reduction potential of the negative electrode solid electrolyte is less than a reduction potential of the positive electrode solid electrolyte layer.

[0046] In combination with the second aspect of the present application, in an optional implementation, the method further comprises: injecting an electrolyte in the shell, and the electrolyte comprises a lithium salt; optionally, the lithium salt comprises at least one of LiPF6, LiClO4, LiBF4, LiFSI, and LiTFSI.

[0047] Compared with the prior art, the embodiments of the present application have the following beneficial effects:

[0048] The lithium battery provided by the embodiments of the present application has the positive electrode solid electrolyte layer in the positive electrode sheet and the negative electrode solid electrolyte layer in the negative electrode sheet arranged oppositely, does not need to arrange a diaphragm, can avoid the influence of the diaphragm on the migration of lithium ions, and eliminate the diffusion impedance generated by the diaphragm; in addition, the positive electrode solid electrolyte layer comprises Li x Al2O3(0 < x < 4), and the negative electrode solid electrolyte layer comprises a negative electrode solid electrolyte and an oxide, wherein the oxide can react with lithium metal to generate a solid electrolyte with similar properties to Li x Al2O3, and the generated solid electrolyte has similar properties to Li x Al2O3, the positive electrode solid electrolyte layer forms a synergistic effect, cooperatively constructs a lithium ion diffusion channel penetrating through the positive electrode and the negative electrode, makes the energy barrier similar when lithium ions migrate, can promote the migration of lithium ions, and the grain boundary resistance of the generated solid electrolyte is smaller, which is more conducive to the migration of lithium ions, so as to effectively improve the rate performance and cycle performance of the lithium battery. In addition, the lithium battery of the present application can effectively reduce the risk of heat runaway caused by leakage of flammable and explosive electrolyte compared with the traditional liquid lithium battery, and has higher safety performance.

[0049] The additional aspects and advantages of the present application will be partially given in the following description, partially become obvious from the following description, or be known by the practice of the present application. BRIEF DESCRIPTION OF DRAWINGS

[0050] The drawings described herein are used to provide further understanding of the present application, constitute a part of the present application, the illustrative embodiments of the present application and the description thereof are used to explain the present application, and do not constitute improper limitation on the present application. In the drawings:

[0051] Figure 1 The flowchart of the preparation method of the lithium battery provided by the embodiments of the present application is shown;

[0052] Figure 2 The scanning electron microscope graph of the cross section of the positive electrode sheet prepared in the embodiment 4 of the present application is shown;

[0053] Figure 3 The scanning electron microscope graph of the cross section of the negative electrode sheet prepared in the embodiment 4 of the present application is shown. DETAILED DESCRIPTION

[0054] In order to make the technical scheme and beneficial effects of the present application more obvious and easy to understand, the following will be described in detail by combining the drawings and listing specific embodiments. It should be understood that these embodiments are only used to illustrate the present application and not to limit the scope of the present application. The experimental methods not specified in the following embodiments are usually carried out according to the conventional experimental conditions. The reagents and raw materials used in the present application are commercially available unless otherwise specified.

[0055] In the following description, numerous specific details are set forth in order to provide a thorough understanding of the present application. However, it will be apparent to one skilled in the art that the present application can be practiced without one or more of these specific details. In other instances, well-known features have not been described in detail to the extent that they would obscure the understanding of the present application. In this document, the terms "computer", "server", "processor", and the like are not limited to just being of the electronic or computer

[0056] The terminology used herein is for the purpose of describing particular embodiments only and is not intended to be limiting of the present application. As used herein, the singular forms "a", "an" and "the" are intended to include the plural forms as well, unless the context clearly indicates otherwise. It will be further understood that the terms "comprises" and / or "comprising", when used in this specification, specify the presence of stated features, integers, steps, operations, elements, and / or components, but do not preclude the presence or addition of one or more other features, integers, steps, operations, elements, components, and / or groups thereof. As used herein, the term "and / or" includes any and all combinations of one or more of the associated listed items.

[0057] For a thorough understanding of the present application, reference will be made to the following detailed description, taken in conjunction with the accompanying drawings, in which: The preferred embodiments of the present application will be described in detail below with reference to the drawings. However, the present application can have other embodiments in addition to those described below.

[0058] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which this application belongs.

[0059] Unless otherwise indicated, the following examples were carried out in accordance with conventional techniques or conditions described in the literature or as recommended by product manufacturers and suppliers. Numerical ranges expressed in the format "from x to y" are understood to include x and y. The endpoints of all ranges directed to the same point are inclusive of that point.

[0060] The embodiments of the present application provide a lithium battery, which includes a shell and an electrode assembly located in the shell, the electrode assembly including a positive electrode sheet and a negative electrode sheet; the positive electrode sheet including a positive electrode current collector, a positive electrode active material layer disposed on a surface of the positive electrode current collector, and a positive electrode solid electrolyte layer disposed on a surface of the positive electrode active material layer away from the positive electrode current collector; the positive electrode solid electrolyte layer including a positive electrode solid electrolyte and an oxide, the oxide being capable of reacting with lithium metal to form the solid electrolyte; and the negative electrode sheet including a negative electrode current collector, a negative electrode active material layer disposed on a surface of the negative electrode current collector, and a negative electrode solid electrolyte layer disposed on a surface of the negative electrode active material layer away from the negative electrode current collector; the negative electrode solid electrolyte layer including a negative electrode solid electrolyte and an oxide, the oxide being capable of reacting with lithium metal to form the solid electrolyte; and the positive electrode solid electrolyte layer and the negative electrode solid electrolyte layer being oppositely disposed. x Al2O3(0<x≤4); the negative electrode sheet including a negative electrode current collector, a negative electrode active material layer disposed on a surface of the negative electrode current collector, and a negative electrode solid electrolyte layer disposed on a surface of the negative electrode active material layer away from the negative electrode current collector; the negative electrode solid electrolyte layer including a negative electrode solid electrolyte and an oxide, the oxide being capable of reacting with lithium metal to form the solid electrolyte; and the positive electrode solid electrolyte layer and the negative electrode solid electrolyte layer being oppositely disposed.

[0061] The lithium battery provided by the embodiments of the present application has the positive solid electrolyte layer in the positive electrode sheet and the negative solid electrolyte layer in the negative electrode sheet arranged oppositely, does not need to arrange a diaphragm, can avoid the influence of the diaphragm on the migration of lithium ions, and eliminates the diffusion impedance generated by the diaphragm. Moreover, the positive solid electrolyte layer includes Li x Al2O3(0 < x < 4), and the negative solid electrolyte layer includes a negative solid electrolyte and an oxide, wherein the oxide can react with lithium metal (lithium metal is formed by lithium ions in the positive electrode material and / or the electrolyte being reduced after obtaining electrons at the negative electrode side) to generate a solid electrolyte with properties similar to Li x Al2O3, and the generated solid electrolyte has properties similar to Li x The positive solid electrolyte layer including Li x Al2O3 forms a synergistic effect to jointly construct a lithium ion diffusion channel penetrating through the positive electrode and the negative electrode, so that the lithium ions have similar energy barriers when migrating, which can promote the migration of lithium ions, and the grain boundary resistance of the generated solid electrolyte is smaller, which is more conducive to the migration of lithium ions, thereby effectively improving the rate performance and cycle performance of the lithium battery. In addition, compared with the traditional liquid lithium battery, the lithium battery of the present application can effectively reduce the risk of heat runaway caused by leakage of flammable and explosive electrolyte, and has high safety performance.

[0062] In the embodiments of the present application, the positive solid electrolyte layer in the positive electrode sheet and the negative solid electrolyte layer in the negative electrode sheet are arranged oppositely in the direction of layering the positive electrode sheet and the negative electrode sheet. The positive solid electrolyte layer and the negative solid electrolyte layer can be directly contacted, or other film layers (such as the polymer layer described in the subsequent embodiments) can be arranged between the positive solid electrolyte layer and the negative solid electrolyte layer.

[0063] In some embodiments, the oxide includes at least one of Al2O3, SnO2, SiO2, TiO2, and ZrO2. The above oxide can react with lithium metal to generate Li-Al-O, Li-Sn-O, Li-Si-O, Li-Ti-O, and Li-Zr-O type solid electrolytes, which have properties similar to Li x Al2O3, and are relatively dense, and have smaller grain boundary resistance. The generated dense solid electrolyte constructs an artificial SEI (Solid Electrolyte Interface) film, which can protect the electrode material from reacting with the electrolyte and avoid the deposition of active metal.

[0064] In some specific embodiments, the oxide includes Al2O3 and / or SnO2.

[0065] During the charging or discharging process of the lithium battery, the structure of the positive active material and the negative active material will change due to the deintercalation of lithium ions, such as expansion or shrinkage, and the SEI film on the surface of the negative electrode will crack and regenerate due to the growth of stress, consuming active lithium. After the reaction of Al2O3 and / or SnO2 with lithium metal, the interlayer interaction changes from van der Waals force to ionic interaction, which can soften the material. The generated soft solid-state electrolyte can better adapt to the stress change of the electrode material, improve the stability of the SEI film, and thus improve the cycle performance of the battery.

[0066] The purpose of introducing the oxide in the present application is to react with lithium to generate a new solid-state electrolyte, thereby promoting the diffusion of lithium ions. When the mass ratio of the oxide to the negative solid-state electrolyte is too low, it will limit the improvement of the lithium ion migration rate; when the mass ratio of the oxide to the negative solid-state electrolyte is too high, it may cause incomplete reaction, that is, there is part of aluminum oxide remaining, which may affect the performance of the lithium battery. Therefore, in some embodiments, the mass ratio of the negative solid-state electrolyte to the oxide is (1:4) to (2:3), for example, it can be 1:4, 1:3, 1:2, 2:3 or any value within the range of any two of the above values. In this way, the overall performance of the lithium battery can be improved.

[0067] In some specific embodiments, the mass percentage of the oxide in the negative solid-state electrolyte layer is 60% to 80%, and the mass percentage of the negative solid-state electrolyte in the negative solid-state electrolyte layer is 20% to 40%.

[0068] In some embodiments, the negative electrode sheet further comprises a polymer layer located on the surface of the negative solid-state electrolyte layer away from the negative active material layer.

[0069] In the embodiments of the present application, by arranging the polymer layer, on the one hand, part of the lithium salt in the positive solid-state electrolyte and the negative solid-state electrolyte, and the solid-state electrolyte generated by the reaction of the oxide in the negative solid-state electrolyte layer with lithium metal, will fill the pores of the polymer, and the polymer layer with high flexibility can better contact the gaps between the positive solid-state electrolyte and the negative solid-state electrolyte particles, improve the interface contact of the positive solid-state electrolyte and the negative solid-state electrolyte, and thus the Li x The positive solid-state electrolyte layer of Al2O3 and the generated solid-state electrolyte can form a better synergistic effect through the polymer layer, further promote the migration of lithium ions, improve the ionic conductivity of the solid-state electrolyte layer, and thus improve the rate performance and cycle performance of the lithium battery; on the other hand, the introduction of the polymer layer can also reduce the self-discharge rate of the battery.

[0070] Optionally, the polymer layer comprises at least one of trimethylene carbonate, polymethyl methacrylate, and polyvinylidene fluoride.

[0071] Optionally, the thickness of the polymer layer can be 3-8 μm, for example, can be 3 μm, 4 μm, 5 μm, 6 μm, 7 μm, 8 μm or any value between any two of the above values. In this way, the interface contact between the positive solid electrolyte and the negative solid electrolyte can be improved by the polymer layer, thereby better promoting the migration of lithium ions, while avoiding the polymer layer being too thick, which excessively prolongs the path of lithium ion migration.

[0072] In some embodiments, the lithium battery further includes an electrolyte, and the electrolyte includes a lithium salt.

[0073] In the embodiments of the present application, the lithium battery including the electrolyte can be referred to as a semi-solid battery, or a hybrid solid-liquid lithium battery. Both solid electrolyte and liquid electrolyte exist in the battery, which can better take advantage of both. First, the liquid electrolyte can be used to fill the pores of the solid electrolyte, which can better improve the solid-solid interface contact and improve the migration of lithium ions, while the barrier function of the solid electrolyte layer can reduce the interface side reaction and prolong the cycle life of the battery. Second, compared with the traditional liquid electrolyte battery, the amount of liquid electrolyte can be greatly reduced, thereby better improving the safety performance of the battery. Third, the battery does not need to set the Overhang area (in the traditional liquid electrolyte battery, it usually refers to the area of the negative electrode sheet beyond the positive electrode sheet), and does not need to set the separator, which can reduce the process difficulty.

[0074] In the case where the negative electrode sheet further includes the polymer layer, the electrolyte can also fill the pores of the polymer layer, and the solid electrolyte generated by aluminum oxide in the negative solid electrolyte layer and metal lithium, and Li x Al2O3, cooperated by the polymer layer, constructs a new ion diffusion channel (such as Li-Al-O layer ion diffusion channel) through the positive electrode, the negative electrode and the electrolyte, and assists the pore filling of the electrolyte, which can greatly improve the migration of lithium ions, thereby significantly improving the rate performance and cycle performance of the lithium battery.

[0075] Optionally, the lithium salt in the electrolyte includes at least one of LiPF6, LiClO4, LiBF4, LiFSI, LiTFSI. The solvent in the electrolyte can include carbonates, for example, including at least one of ethylene carbonate (EC), dimethyl carbonate (DMC), propylene carbonate (PC), ethyl methyl carbonate (EMC).

[0076] In some embodiments, the lithium salt in the electrolyte includes LiFSI, or includes LiTFSI and LiPF6. LiFSI and LiTFSI have large anion groups and have strong affinity with the fluorine-containing segments of the polymer, showing a plasticizing effect on the polymer. High concentration of lithium salt continuously promotes the polymer to transform from an ordered structure to an amorphous structure, expands the proportion of the amorphous region in the polymer, and a TFSI - LiTFSI can be combined with two or more Li + coordination, thereby facilitating the enhancement of ion binding capacity and the acceleration of lithium ion transmission. LiTFSI may, at about 4.2V, cause corrosion to commonly used current collectors such as aluminum foil. The present application, through the combined action of the dual lithium salt LiPF6 and LiTFSI and the introduction of high-voltage-resistant solid electrolytes (such as NASICON-type solid electrolytes), can passivate the anion, inhibit the corrosion damage that may be caused by LITFSI, and increase the use voltage of the battery.

[0077] In some embodiments, the positive electrode solid electrolyte layer further includes a NASICON-type solid electrolyte and / or a perovskite-type solid electrolyte. This facilitates the improvement of the ionic conductivity of the positive electrode solid electrolyte layer.

[0078] For example, the NASICON-type solid electrolyte can include Li 1+x Al x Ti 2x (PO4)3(0≤x≤0.5), and the perovskite-type solid electrolyte can include ATiO3(A = Ca, Sr, Ba).

[0079] Further, the mass ratio of the NASICON-type solid electrolyte and / or the perovskite-type solid electrolyte to Li x Al2O3 is (4:1) to (3:2), for example, can be 4:1, 3:1, 2:1, 3:2, or any value within the range between any two of the above values. This facilitates the consideration of both the high ionic conductivity of the positive electrode solid electrolyte layer and the guarantee of similar energy barriers for lithium ions to migrate between the positive and negative electrodes, facilitating the migration of lithium ions and facilitating fast deintercalation.

[0080] It should be noted that when the positive electrode solid electrolyte layer further includes one of a NASICON-type solid electrolyte and a perovskite-type solid electrolyte, the mass ratio of the NASICON-type solid electrolyte or the perovskite-type solid electrolyte to Li x Al2O3 is (4:1) to (3:2); and when the positive electrode solid electrolyte layer further includes both a NASICON-type solid electrolyte and a perovskite-type solid electrolyte, the total mass of the NASICON-type solid electrolyte and the perovskite-type solid electrolyte to Li xThe mass ratio of Al2O3 is (4:1) to (3:2).

[0081] In some embodiments, the positive solid electrolyte layer comprises Li 1.3 Al 0.3 Ti 1.7 (PO4)3 and Li 3.4 Al2O3, Li 1.3 Al 0.3 Ti 1.7 (PO4)3 in the positive solid electrolyte layer is 60% to 80%, and Li 3.4 Al2O3 in the positive solid electrolyte layer is 20% to 40%. This is conducive to further promoting the migration of lithium ions, thereby further improving the rate performance and cycle performance of the lithium battery.

[0082] In some embodiments, the reduction potential of the negative solid electrolyte is less than the reduction potential of the positive solid electrolyte layer. This is conducive to improving the safety, stability and cycle life of the lithium battery.

[0083] In some embodiments, the negative solid electrolyte comprises a garnet-type solid electrolyte. Because the garnet-type solid electrolyte is relatively stable and is not easily reduced by lithium metal, it can avoid excessive consumption in the cycle, thereby being conducive to prolonging the electrolyte life.

[0084] In the embodiments of the present application, the positive solid electrolyte layer and the negative solid electrolyte layer can play a role in supplementing the active lithium ions lost in the cycle, and can also inhibit the dissolution of transition metal ions and avoid the deposition of transition metal ions on the negative side, thereby reducing the loss of active metal, improving the cycle stability and prolonging the cycle life of the battery.

[0085] In some embodiments, the thickness of the negative solid electrolyte layer is 5 μm to 15 μm, for example, it can be 5 μm, 10 μm, 15 μm or any value within the range between any two of the above values.

[0086] In some embodiments, the thickness of the positive solid electrolyte layer is 5 μm to 15 μm, for example, it can be 5 μm, 10 μm, 15 μm or any value within the range between any two of the above values.

[0087] Controlling the thickness of the negative solid electrolyte layer and the positive solid electrolyte layer within the above range is conducive to improving the overall electrochemical performance and safety performance of the lithium battery.

[0088] In some embodiments, the thickness of the positive electrode active material layer is 80 μm to 250 μm, for example, can be 80 μm, 100 μm, 120 μm, 140 μm, 160 μm, 180 μm, 200 μm, 220 μm, 250 μm or any value within any two of the above-mentioned value ranges.

[0089] In some embodiments, the thickness of the negative electrode active material layer is 70 μm to 200 μm, for example, can be 70 μm, 100 μm, 130 μm, 160 μm, 200 μm or any value within any two of the above-mentioned value ranges.

[0090] Controlling the thickness of the positive electrode active material layer and the negative electrode active material layer within the above-mentioned ranges is beneficial to improve the capacity of the lithium battery.

[0091] In the embodiments of the present application, the negative electrode active material layer comprises a negative electrode active material. For example, the negative electrode active material comprises at least one of graphite, silicon-oxygen material, silicon-carbon material and lithium metal. The positive electrode active material layer comprises a positive electrode active material. For example, the positive electrode active material comprises at least one of ternary nickel-cobalt-manganese, ternary nickel-cobalt-aluminum, lithium iron phosphate, lithium cobaltate, lithium-rich manganese-based and lithium manganate.

[0092] The shell of the lithium battery is not particularly limited in the present application, and a battery shell known in the art can be used.

[0093] The embodiments of the present application also provide a preparation method of a lithium battery, which is described in detail as follows. Figure 1 The preparation method of the lithium battery provided by the embodiments of the present application comprises the following steps:

[0094] S1: sequentially forming a positive electrode active material layer and a positive electrode solid electrolyte layer on the surface of the positive electrode current collector, the positive electrode solid electrolyte layer comprising Li x Al2O3(0<x≤4), to obtain a positive electrode sheet;

[0095] S2: sequentially forming a negative electrode active material layer and a negative electrode solid electrolyte layer on the surface of the negative electrode current collector, the negative electrode solid electrolyte layer comprising a negative electrode solid electrolyte and an oxide, the oxide being capable of reacting with lithium metal to generate a solid electrolyte, to obtain a negative electrode sheet;

[0096] S3: assembling the positive electrode sheet and the negative electrode sheet to obtain an electrode assembly; wherein the positive electrode solid electrolyte layer and the negative electrode solid electrolyte layer are oppositely arranged;

[0097] S4: placing the electrode assembly in a shell to obtain a lithium battery.

[0098] The positive electrode sheet prepared in the embodiments of the present application comprises a positive electrode solid electrolyte layer, and the negative electrode sheet prepared comprises a negative electrode solid electrolyte layer. When the positive electrode sheet and the negative electrode sheet are assembled, the positive electrode solid electrolyte layer in the positive electrode sheet and the negative electrode solid electrolyte layer in the negative electrode sheet are arranged oppositely, without the need to arrange a separator, which can avoid the influence of the separator on the migration of lithium ions and eliminate the diffusion impedance generated by the separator. Moreover, the positive electrode solid electrolyte layer comprises Li x Al2O3(0 < x < 4), and the negative electrode solid electrolyte layer comprises a negative electrode solid electrolyte and an oxide, wherein the oxide can react with lithium metal to generate a solid electrolyte with properties similar to Li x Al2O3, and the generated solid electrolyte and the positive electrode solid electrolyte layer comprising Li x Al2O3 form a synergistic effect and jointly construct a lithium ion diffusion channel penetrating through the positive and negative electrodes, so that the lithium ion migration has similar energy barriers, which can promote the migration of lithium ions, and the grain boundary resistance of the generated solid electrolyte is smaller, which is more conducive to the migration of lithium ions, thereby effectively improving the rate performance and cycle performance of the lithium battery. In addition, the lithium battery of the present application can effectively reduce the risk of heat runaway caused by leakage of flammable and explosive electrolyte compared with the traditional liquid lithium battery, and has higher safety performance.

[0099] It should be understood that, although each step in the above flowchart is displayed in sequence according to the direction of the arrow, these steps are not necessarily executed in sequence according to the direction of the arrow. Moreover, at least part of the steps in the above flowchart can include multiple steps or multiple stages, which are not necessarily executed at the same time or in sequence.

[0100] The steps for preparing the positive electrode sheet in step S1 can include:

[0101] Step S11: First, the positive electrode binder (specifically, for example, PVDF) is added to the solvent (specifically, for example, NMP), and after stirring, a glue solution is obtained. Next, the conductive agent (specifically, for example, conductive carbon SP) and the positive electrode active material are added to the glue solution, and the positive electrode active slurry is continuously stirred and dispersed to form a positive electrode active material layer. Then, the positive electrode active material layer is coated on the surface of the positive electrode current collector (specifically, for example, aluminum foil), and after drying, the positive electrode active material layer is formed. Exemplarily, the positive electrode active material includes at least one of ternary nickel-cobalt-manganese, ternary nickel-cobalt-aluminum, lithium iron phosphate, lithium cobaltate, lithium-rich manganese-based, and lithium manganate.

[0102] Step S12: First, the positive electrode binder (specifically, for example, PVDF) and Li x Al2O3 are added to the solvent (specifically, for example, NMP), and after high-speed dispersion, the positive electrode electrolyte slurry is obtained. The positive electrode electrolyte slurry is coated on the surface of the positive electrode active material layer, and after drying, the positive electrode solid electrolyte layer is formed.

[0103] In the process of preparing the positive electrode electrolyte slurry in step S12, the NASICON solid electrolyte and / or the perovskite solid electrolyte can also be added, that is, the prepared positive electrode solid electrolyte layer can also include the NASICON solid electrolyte and / or the perovskite solid electrolyte. In this way, the ionic conductivity of the positive electrode solid electrolyte layer is improved.

[0104] Further, the mass ratio of the NASICON solid electrolyte and / or the perovskite solid electrolyte to Li x The mass ratio of Al2O3 to Li

[0105] It should be noted that when the positive electrode solid electrolyte layer further includes one of the NASICON solid electrolyte and the perovskite solid electrolyte, the mass ratio of the NASICON solid electrolyte or the perovskite solid electrolyte to Li x Al2O3 is (4:1) to (3:2); when the positive electrode solid electrolyte layer further includes both the NASICON solid electrolyte and the perovskite solid electrolyte, the total mass of the NASICON solid electrolyte and the perovskite solid electrolyte to Li x Al2O3 is (4:1) to (3:2).

[0106] In some specific embodiments, the positive electrode solid electrolyte layer includes Li 1.3 Al 0.3 Ti 1.7 (PO4)3 and Li 3.4 Al2O3, Li 1.3 Al 0.3 Ti 1.7 (PO4)3 accounts for 60% to 80% of the mass of the positive electrode solid electrolyte layer, and Li 3.4 Al2O3 accounts for 20% to 40% of the mass of the positive electrode solid electrolyte layer. In this way, the migration of lithium ions is further promoted, thereby further improving the rate performance and cycle performance of the lithium battery.

[0107] In the positive electrode sheet prepared in step S1, the thickness of the positive electrode solid electrolyte layer can be 5 μm to 15 μm.

[0108] In the positive electrode sheet prepared in step S1, the thickness of the positive electrode active material layer can be 80 μm to 250 μm.

[0109] The step of preparing the negative electrode sheet in step S2 can include:

[0110] Step S21: first, a first negative electrode binder (specifically, for example, CMC) is added to a solvent (specifically, for example, deionized water), and after stirring, a glue solution is obtained, then, a conductive agent (specifically, for example, conductive carbon SP) and a negative electrode active material are added to the glue solution, and continue to be dispersed by stirring, then, a second negative electrode binder (specifically, for example, SBR) is added, and after dispersion, a negative electrode active slurry is formed, then, the negative electrode active slurry is coated on the surface of the negative electrode current collector (specifically, for example, a copper foil), and after drying, a negative electrode active material layer is formed; for example, the negative electrode active material includes at least one of graphite, silicon-oxygen material, silicon-carbon material, and lithium metal.

[0111] Step S22: first, a negative electrode binder (specifically, for example, PVDF), a negative electrode solid electrolyte, and an oxide are added to a solvent (specifically, for example, deionized water), and after high-speed dispersion, a negative electrode electrolyte slurry is obtained, then, the negative electrode electrolyte slurry is coated on the surface of the negative electrode active material layer, and after drying, a negative electrode solid electrolyte layer is formed.

[0112] In step S22, the oxide includes at least one of Al2O3, SnO2, SiO2, TiO2, and ZrO2, for example. The above-mentioned oxide can react with lithium metal to generate Li-Al-O, Li-Sn-O, Li-Si-O, Li-Ti-O, and Li-Zr-O type solid electrolytes, which have a higher ionic conductivity than LiPON and can be used as a solid electrolyte. x Al2O3 has similar properties and is relatively dense, and has a smaller grain boundary resistance. The generated dense solid electrolyte constructs an artificial SEI (Solid Electrolyte Interface) film, which can protect the electrode material from reacting with the electrolyte and avoid the deposition of active metal.

[0113] In some specific embodiments, the oxide includes Al2O3 and / or SnO2.

[0114] After Al2O3 and / or SnO2 reacts with lithium metal, the interlayer action changes from van der Waals force to ionic interaction, which can play a role in softening the material. The generated soft solid electrolyte can better adapt to the changes in the stress of the electrode material, improve the stability of the SEI film, and thus improve the cycle performance of the battery.

[0115] The oxide is introduced to react with lithium to generate a new solid-state electrolyte, thereby facilitating the diffusion of lithium ions. When the mass ratio of the oxide to the negative solid-state electrolyte is too low, the improvement of the lithium ion migration rate will be limited; when the mass ratio of the oxide to the negative solid-state electrolyte is too high, an incomplete reaction may be triggered, i.e., there is a part of aluminum oxide remaining, which may affect the performance of the lithium battery. Therefore, in some embodiments, the mass ratio of the negative solid-state electrolyte to the oxide is (1:4) to (2:3), for example, it can be 1:4, 1:3, 1:2, 2:3, or any value within the range of any two of the above values. In this way, the overall performance of the lithium battery can be improved.

[0116] In some specific embodiments, the mass ratio of the oxide in the negative solid-state electrolyte layer is 60% to 80%, and the mass ratio of the negative solid-state electrolyte in the negative solid-state electrolyte layer is 20% to 40%.

[0117] In some embodiments, after step S22, the preparation of the negative electrode sheet can further include forming a polymer layer on the side surface of the negative solid-state electrolyte layer away from the negative active material layer. By forming the polymer layer, on the one hand, part of the lithium salt in the positive solid-state electrolyte and the negative solid-state electrolyte, and the oxide in the negative solid-state electrolyte layer and the solid-state electrolyte generated by the reaction of the lithium metal will fill the pores of the polymer, and the polymer layer with high flexibility can better contact the gap between the positive solid-state electrolyte and the negative solid-state electrolyte particles, thereby improving the interface contact of the positive solid-state electrolyte and the negative solid-state electrolyte. In this way, the Li x The positive solid-state electrolyte layer of Al2O3 and the generated solid-state electrolyte can form a better synergy through the polymer layer, further facilitating the migration of lithium ions and improving the ionic conductivity of the solid-state electrolyte layer, thereby improving the rate performance and cycle performance of the lithium battery; on the other hand, the introduction of the polymer layer can also reduce the self-discharge rate of the battery.

[0118] In the actual preparation process, forming the polymer layer can include: first, dissolving the polymer in a solvent to form a mixed solution, ball-milling the mixed solution, and then coating the surface of the base film, and after drying, a polymer layer is formed; then, the polymer layer is transferred to the side surface of the negative solid-state electrolyte layer away from the negative active material layer.

[0119] The polymer includes, for example, at least one of trimethylene carbonate, polymethyl methacrylate, and polyvinylidene fluoride. The solvent includes, for example, cyclic carbonate and methylpyrrolidone. The time of the ball milling treatment is, for example, 45 min to 75 min. The base film includes, for example, a polyethylene terephthalate (PET) film. The temperature of the drying treatment can be 60°C to 70°C. The time of the drying can be 10 h to 14 h. The manner of transferring the polymer layer to the surface of the negative solid electrolyte layer can be roll-to-roll pressing of the polymer layer to the surface of the negative solid electrolyte layer.

[0120] Optionally, the thickness of the polymer layer is 3 μm to 8 μm, for example, 3 μm, 4 μm, 5 μm, 6 μm, 7 μm, 8 μm, or any value within a range between any two of the above values. This can better improve the interface contact between the positive solid electrolyte and the negative solid electrolyte through the polymer layer, thereby better promoting the migration of lithium ions, while avoiding an excessively thick polymer layer that excessively prolongs the path of lithium ion migration.

[0121] In step S2, the reduction potential of the negative solid electrolyte can be less than the reduction potential of the positive solid electrolyte layer. This is conducive to improving the safety, stability, and cycle life of the lithium battery.

[0122] Further, the negative solid electrolyte can include a garnet solid electrolyte. Because the garnet solid electrolyte is relatively stable and is not easily reduced by lithium metal, it can avoid excessive consumption in the cycle, thereby being conducive to prolonging the electrolyte life.

[0123] In the negative electrode sheet prepared in step S2, the thickness of the negative solid electrolyte layer can be 5 μm to 15 μm.

[0124] In the negative electrode sheet prepared in step S2, the thickness of the negative active material layer can be 70 μm to 200 μm.

[0125] In some embodiments, the method of preparing the lithium battery can further include: injecting an electrolyte into the shell, the electrolyte including a lithium salt.

[0126] In the embodiment of the present application, the lithium battery including the electrolyte can be called a semi-solid battery, or a hybrid solid-liquid lithium battery. Both solid electrolytes and liquid electrolytes exist in the battery, which can better take into account the advantages of both. First, filling the pores of the solid electrolyte with a liquid electrolyte can better improve the solid-solid interface contact, so that the migration of lithium ions is improved. At the same time, the barrier function of the solid electrolyte layer can be used to reduce the side reactions at the interface and extend the cycle life of the battery. Secondly, compared with traditional liquid electrolyte batteries, the amount of liquid electrolyte injection can be greatly reduced, thereby improving the safety performance of the battery. Furthermore, there is no need to set an Overhang area in the battery (in traditional liquid electrolyte batteries, it usually refers to the area where the negative electrode sheet exceeds the positive electrode sheet), and there is no need to set a diaphragm, which can reduce the difficulty of the process.

[0127] In the case where the negative electrode sheet prepared in step S2 also includes the above-mentioned polymer layer, the electrolyte can also fill the pores of the polymer layer, and the solid electrolyte generated by aluminum oxide and metallic lithium in the negative electrode solid electrolyte layer and the Li in the positive electrode solid electrolyte layer x Al2O3, through the synergistic effect of the polymer layer, constructs new ion diffusion channels (such as Li-Al-O layer ion diffusion channels) that run through the positive electrode, negative electrode and electrolyte, assisting in filling the pores of the electrolyte, which can qualitatively improve the migration of lithium ions, thereby significantly improving the rate performance and cycle performance of lithium batteries.

[0128] Optionally, the lithium salt in the electrolyte includes at least one of LiPF6, LiClO4, LiBF4, LiFSI, and LiTFSI. The solvent in the electrolyte may include a carbonate ester, specifically, for example, at least one of ethylene carbonate (EC), dimethyl carbonate (DMC), propylene carbonate (PC), carboxylic acid ester (EA), and ethyl methyl carbonate (EMC).

[0129] In some embodiments, the lithium salt in the electrolyte includes LiFSI, or includes LiTFSI and LiPF6. LiFSI and LiTFSI have larger anionic groups and have strong affinity with the fluorine-containing segments of the polymer, showing a plasticizing effect on the polymer. High concentrations of lithium salts continuously promote the transformation of the polymer from an ordered structure to an amorphous structure, increasing the proportion of amorphous regions in the polymer, and a TFSI - Can be used with two or more Li +The coordination facilitates the enhancement of ion binding capacity and the acceleration of lithium ion transmission. LiTFSI may cause corrosion to the commonly used current collector aluminum foil at about 4.2 V. The present application can passivate the anion by the combined action of the dual lithium salt LiPF6 and LiTFSI and the introduction of high-voltage-resistant solid electrolyte (for example, NASICON-type solid electrolyte), inhibit the corrosion and damage effect of LITFSI, and improve the battery use voltage.

[0130] The shell of the lithium battery in the present application is not particularly limited and a battery shell known in the art can be used.

[0131] The technical solutions of the present application will be further described below in combination with multiple examples and comparative examples.

[0132] Example 1

[0133] The preparation method of the lithium battery in the present embodiment includes the following steps:

[0134] Step S101: add the binder PVDF into the NMP solution, stir at high speed for 4 h, and obtain the PVDF glue solution after standing, then add the conductive agent SP and the nickel-cobalt-manganese ternary material NCM into the glue solution in sequence, continue to stir and disperse to form the positive electrode active slurry, wherein the mass ratio of PVDF, SP and NCM is 2.5:1.8:95.7, then coat the positive electrode active slurry on the surface of the aluminum foil, dry to form the positive electrode active material layer; add PVDF into the NMP solution, then add Li 1.3 Al 0.3 Ti 1.7 a mixture of (PO4)3(LATP) and Li 3.4 Al2O3, wherein the mass ratio of PVDF to the mixture of LATP and Li 3.4 Al2O3 is 10:90 (the mass ratio of LATP to Li 3.4 Al2O3 is 4:1), obtain the positive electrode electrolyte slurry after high-speed dispersion, coat the positive electrode electrolyte slurry on the surface of the positive electrode active material layer, dry to form the positive electrode solid electrolyte layer, and obtain the positive electrode sheet;

[0135] Step S102: add the binder CMC into deionized water, disperse for 4.5 h at a medium speed, obtain the CMC glue solution after standing, then add the conductive agent SP and the graphite in sequence, continue to disperse, finally add the binder SBR, obtain the negative electrode active slurry after dispersion, wherein the mass ratio of CMC, SP, graphite and SBR is 1.8:1.2:95.4:1.6, coat the negative electrode active slurry on the surface of the copper foil, dry to form the negative electrode active material layer; add the binder PVDF into the NMP solution, then add the mixture of lithium lanthanum zirconium oxide LLZO (garnet solid electrolyte) and Al2O3, wherein the mass ratio of PVDF to the mixture of LLZO and Al2O3 is 10:90 (the mass ratio of LLZO to Al2O3 is 1:4), obtain the negative electrode electrolyte slurry after high-speed dispersion, coat the negative electrode electrolyte slurry on the surface of the negative electrode active material layer, dry to form the negative electrode solid electrolyte layer;

[0136] Step S103: dissolve the trimethylene carbonate into the mixture of cyclic carbonate and methyl pyrrolidone to form a mixed solution, wet ball mill for 60 min, coat the slurry after ball milling on the surface of the PET substrate, vacuum dry at 65℃ for 12 h to obtain a polymer layer, then transfer the polymer layer to the surface of the negative electrode solid electrolyte layer by using pressure transfer to obtain a negative electrode sheet;

[0137] Step S104: slice the positive electrode sheet prepared in step S101 and the negative electrode sheet prepared in step S103, then stack them in the order of negative electrode-positive electrode-negative electrode-positive electrode-negative electrode in sequence, fix the position of the electrode sheet by using adhesive tape, then weld the tabs, then package in an aluminum-plastic film, after drying, inject the electrolyte, wherein the electrolyte is a solution of LiPF6 and LiTFSI in a mixed solvent of EA, EC and EMC (the volume ratio of EA, EC and EMC is 1:1:1), the mass fraction of LiPF6 and LiTFSI is 95% and 5% respectively, after secondary packaging and exhausting, obtain a lithium battery.

[0138] Example 2

[0139] The preparation method of the lithium battery in this example is basically the same as that in example 1, the difference lies in that:

[0140] In step S102, the mass ratio of LLZO to Al2O3 is adjusted to 3:7.

[0141] Example 3

[0142] The preparation method of the lithium battery in this example is basically the same as that in example 1, the difference lies in that:

[0143] In step S102, the mass ratio of LLZO to Al2O3 is adjusted to 2:3.

[0144] Example 4

[0145] The preparation method of the lithium battery in this embodiment is basically the same as that in Embodiment 1, except that:

[0146] Step S103 is omitted, that is, the prepared negative electrode sheet does not contain the polymer layer formed on the surface of the negative electrode solid electrolyte layer.

[0147] Embodiment 5

[0148] The preparation method of the lithium battery in this embodiment is basically the same as that in Embodiment 1, except that:

[0149] In step S102, the mass ratio of LLZO and Al2O3 is adjusted to 4:1.

[0150] Embodiment 6

[0151] The preparation method of the lithium battery in this embodiment is basically the same as that in Embodiment 1, except that:

[0152] The LATP in step S101 is adjusted to LLZO.

[0153] Embodiment 7

[0154] The preparation method of the lithium battery in this embodiment is basically the same as that in Embodiment 1, except that:

[0155] The LLZO in step S102 is adjusted to lithium lanthanum titanium oxide LLTO (perovskite solid electrolyte).

[0156] Comparative Example 1

[0157] The preparation method of the lithium battery in this embodiment is basically the same as that in Embodiment 1, except that:

[0158] In step S102, the step of forming a negative electrode solid electrolyte layer on the surface of the negative electrode active material layer is omitted, and step S103 is also omitted, that is, the prepared negative electrode sheet only contains a negative electrode current collector copper foil and a negative electrode active material layer on the copper foil.

[0159] Comparative Example 2

[0160] The preparation method of the lithium battery in this embodiment is basically the same as that in Embodiment 1, except that:

[0161] In step S102, no Al2O3 is added during the preparation of the negative electrode electrolyte slurry.

[0162] Comparative Example 3

[0163] The preparation method of the lithium battery in this embodiment is basically the same as that in Embodiment 1, except that:

[0164] In step S102, no LLZO is added during the preparation of the negative electrode electrolyte slurry.

[0165] The scanning electron microscope images of the cross sections of the positive electrode sheet and the negative electrode sheet prepared in Example 4 above are shown in Figure 2 and Figure 3 It can be seen from Figure 2 and Figure 3 that the interface between the positive electrode solid electrolyte layer and the positive electrode active material layer in the positive electrode sheet is in good contact, and the interface between the negative electrode solid electrolyte layer and the negative electrode active material layer in the negative electrode sheet is in good contact.

[0166] The lithium batteries prepared in each of the above examples and each of the comparative examples were tested as follows:

[0167] (1) Cycle 1500 cycle capacity retention rate test: at a set temperature (25℃, 45℃), after standing for 30 min, charge to 4.25V at 1C constant current and constant voltage, and the cutoff current is 0.05C. After standing for 30 min, discharge to 2.5V, cycle 3 times of charging and discharging, and the average value is CO, which is marked as the cell capacity. According to the above charging and discharging process, cycle 1500 times, the discharge capacity of the 1500th cycle is marked as C1500, and the capacity retention rate of 1500 cycles is (C1500 / C0)*100%.

[0168] (2) 5C charging constant current ratio: the 5C charging constant current ratio refers to the ratio of the amount of electricity charged by constant current to the total amount of electricity charged by constant current and constant voltage when the battery monomer is charged. The greater the constant current ratio, the smaller the polarization degree of the battery charging, that is, the better the rate performance of the battery. The specific test method is as follows: at 25℃, charge to 4.25V at 5C constant current and constant voltage, the cutoff current is 0.05C, the constant current and constant voltage charging capacity is marked as A, the capacity of the constant current section is marked as B, and the constant current ratio is (B / A)*100%.

[0169] The test results of the above tests are shown in Table 1.

[0170] Table 1

[0171]

[0172]

[0173] As can be seen from the data in Table 1, in the lithium battery negative plate of Comparative Example 1, no negative solid-state electrolyte layer including negative solid-state electrolyte and oxide is formed on the surface of the negative active material layer, and the capacity retention rate after 1500 cycles at 45°C and the 5C charging constant current ratio are significantly reduced compared with Example 1. In the lithium battery negative plate of Comparative Example 2, although a negative solid-state electrolyte layer is formed on the surface of the negative active material layer, since the negative solid-state electrolyte layer only contains negative solid-state electrolyte and does not contain oxide, the capacity retention rate after 1500 cycles and the 5C charging constant current ratio are significantly reduced compared with Example 1. In the lithium battery negative plate of Comparative Example 3, although a negative solid-state electrolyte layer is formed on the surface of the negative active material layer, since the negative solid-state electrolyte layer only contains oxide and does not contain negative solid-state electrolyte, the capacity retention rate after 1500 cycles and the 5C charging constant current ratio are significantly reduced compared with Example 1. The capacity retention rate after 1500 cycles and the 5C charging constant current ratio of the lithium battery of Examples 1 to 5 are all at a high level. This shows that the lithium battery without a separator in the present application can avoid the influence of the separator on the migration of lithium ions and eliminate the diffusion impedance generated by the separator; moreover, the positive solid-state electrolyte layer includes Li x Al2O3(0 < x < 4), and the negative solid-state electrolyte layer includes negative solid-state electrolyte and oxide, wherein the oxide can react with lithium metal to generate a solid-state electrolyte with properties similar to Li x Al2O3, and the generated solid-state electrolyte has properties similar to Li x Al2O3, and the generated solid-state electrolyte has properties similar to Li

[0174] As can be seen from the data in Table 1, the lithium battery negative plate of Example 4 does not contain a polymer layer formed on the surface of the negative solid-state electrolyte layer, although the 5C charging constant current ratio of the lithium battery is high, the capacity retention rate after 1500 cycles is reduced compared with Example 1, especially the capacity retention rate after 1500 cycles at high temperature (45°C) is significantly reduced. This shows that in the lithium battery negative plate of the present application, it is a better technical solution to contain a polymer layer formed on the surface of the negative solid-state electrolyte layer.

[0175] As can be seen from the data in Table 1, in the lithium battery negative plate of Example 5, the mass ratio of LLZO and Al2O3 is adjusted to 4:1, and the cycle 1500 cycle capacity retention rate and 5C charging constant current ratio of the lithium battery are slightly decreased compared with Examples 1 to 3, thereby indicating that the mass ratio of the negative electrode solid-state electrolyte to the oxide in the negative electrode plate of the lithium battery of the present application is (1:4) to (2:3), which is a relatively optimal technical solution.

[0176] As can be seen from the data in Table 1, in the lithium battery negative plate of Example 7, the negative electrode solid-state electrolyte is adjusted from LLZO (garnet-type solid-state electrolyte) to LLTO (perovskite-type solid-state electrolyte), and the cycle 1500 cycle capacity retention rate and 5C charging constant current ratio of the lithium battery are at a relatively high level, but are slightly decreased compared with other examples, thereby indicating that the garnet-type solid-state electrolyte is a relatively optimal technical solution for the negative electrode solid-state electrolyte in the negative electrode plate of the lithium battery of the present application.

[0177] It should be noted that the lithium battery embodiments provided by the present application and the preparation method embodiments of the lithium battery belong to the same concept; the technical features in the technical solutions recorded in each embodiment can be arbitrarily combined without conflict.

[0178] It should be understood that the above embodiments are exemplary and are not intended to include all possible implementations. Various modifications and changes can also be made to the above embodiments without departing from the scope of the present disclosure. Similarly, various technical features of the above embodiments can also be arbitrarily combined to form additional embodiments of the present application that have not been explicitly described. Therefore, the above embodiments only express several implementation manners of the present application, and do not limit the protection scope of the patent of the present application.

Claims

1. A lithium battery, characterized in that: It includes a shell and an electrode assembly located in the shell, wherein the electrode assembly includes a positive electrode sheet and a negative electrode sheet; The positive electrode sheet includes a positive electrode current collector, a positive electrode active material layer arranged on the surface of the positive electrode current collector, and a positive electrode solid electrolyte layer arranged on the surface of the positive electrode active material layer away from the positive electrode current collector; the positive electrode solid electrolyte layer includes Li x Al2O3(0<x≤4); The negative electrode sheet includes a negative electrode current collector, a negative electrode active material layer disposed on the surface of the negative electrode current collector, and a negative electrode solid electrolyte layer disposed on the surface of the negative electrode active material layer on a side away from the negative electrode current collector; the negative electrode solid electrolyte layer includes a negative electrode solid electrolyte and an oxide, and the oxide can react with lithium metal to form a solid electrolyte; The positive electrode solid electrolyte layer and the negative electrode solid electrolyte layer are arranged opposite to each other.

2. The lithium battery according to claim 1, characterized in that The negative electrode sheet also includes a polymer layer located on the surface of the negative electrode solid electrolyte layer away from the negative electrode active material layer; optionally, the polymer layer includes at least one of trimethylene carbonate, polymethyl methacrylate, and polyvinylidene fluoride; optionally, the thickness of the polymer layer is 3μm to 8μm.

3. The lithium battery according to claim 1 or 2, characterized in that The positive electrode sheet satisfies at least one of the following characteristics: (1) The positive electrode solid electrolyte layer further includes a NASICON type solid electrolyte and / or a perovskite type solid electrolyte; optionally, the mass of the NASICON type solid electrolyte and / or the perovskite type solid electrolyte is the same as that of the Li x The mass ratio of Al2O3 is (4:1) to (3:2); (2) The positive electrode active material layer includes a positive electrode active material, and the positive electrode active material includes at least one of ternary nickel-cobalt-manganese, ternary nickel-cobalt-aluminum, lithium iron phosphate, lithium cobalt oxide, lithium-rich manganese matrix, and lithium manganate; (3) The thickness of the positive electrode solid electrolyte layer is 5 μm to 15 μm; (4) The thickness of the positive electrode active material layer is 80 μm to 250 μm.

4. The lithium battery according to claim 1 or 2, characterized in that The negative electrode sheet satisfies at least one of the following characteristics: (1) The negative electrode solid electrolyte includes a garnet-type solid electrolyte; (2) The oxide includes at least one of Al2O3, SnO2, SiO2, TiO2, and ZrO2; (3) The mass ratio of the negative electrode solid electrolyte to the mass of the oxide is (1:4) to (2:3); (4) The negative electrode active material layer includes a negative electrode active material, and the negative electrode active material includes at least one of graphite, silicon oxide material, silicon carbon material, and lithium metal; (5) The thickness of the negative electrode solid electrolyte layer is 5 μm to 15 μm; (6) The thickness of the negative electrode active material layer is 70 μm to 200 μm; (7) The reduction potential of the negative electrode solid electrolyte is lower than the reduction potential of the positive electrode solid electrolyte layer.

5. The lithium battery according to claim 1 or 2, characterized in that The lithium battery further includes an electrolyte, and the electrolyte includes a lithium salt; optionally, the lithium salt includes at least one of LiPF6, LiClO4, LiBF4, LiFSI, and LiTFSI.

6. A method for preparing a lithium battery, characterized in that: The method comprises the following steps: A positive electrode active material layer and a positive electrode solid electrolyte layer are sequentially formed on the surface of the positive electrode current collector, wherein the positive electrode solid electrolyte layer includes Li x Al2O3 (0<x≤4), to obtain a positive electrode sheet; forming a negative electrode active material layer and a negative electrode solid electrolyte layer in sequence on the surface of the negative electrode current collector, wherein the negative electrode solid electrolyte layer comprises a negative electrode solid electrolyte and an oxide, wherein the oxide can react with lithium metal to form a solid electrolyte to obtain a negative electrode sheet; Assembling the positive electrode sheet and the negative electrode sheet to obtain an electrode assembly; wherein the positive electrode solid electrolyte layer and the negative electrode solid electrolyte layer are arranged opposite to each other; The electrode assembly is placed in a shell to obtain the lithium battery.

7. The method for preparing a lithium battery according to claim 6, wherein: The preparation of the negative electrode sheet further includes forming a polymer layer on a surface of the negative electrode solid electrolyte layer away from the negative electrode active material layer; optionally, the thickness of the polymer layer is 3 μm to 8 μm; optionally, forming the polymer layer includes: dissolving a polymer in a solvent to form a mixed solution, ball-milling the mixed solution, coating the mixed solution on the surface of the base film, and drying the mixed solution to form a polymer layer; the polymer comprises at least one of trimethylene carbonate, polymethyl methacrylate, and polyvinylidene fluoride; The polymer layer is transferred to the surface of the negative electrode solid electrolyte layer on a side away from the negative electrode active material layer.

8. The method for preparing a lithium battery according to claim 6 or 7, wherein: The positive electrode sheet is prepared to meet at least one of the following characteristics: (1) The positive electrode solid electrolyte layer further includes a NASICON type solid electrolyte and / or a perovskite type solid electrolyte; optionally, the mass of the NASICON type solid electrolyte and / or the perovskite type solid electrolyte is the same as that of the Li x The mass ratio of Al2O3 is (4:1) to (3:2); (2) The positive electrode active material layer includes a positive electrode active material, and the positive electrode active material includes at least one of ternary nickel-cobalt-manganese, ternary nickel-cobalt-aluminum, lithium iron phosphate, lithium cobalt oxide, lithium-rich manganese matrix, and lithium manganate; (3) The thickness of the positive electrode solid electrolyte layer is 5 μm to 15 μm; (4) The thickness of the positive electrode active material layer is 80 μm to 250 μm.

9. The method for preparing a lithium battery according to claim 6 or 7, wherein: The negative electrode sheet is prepared to meet at least one of the following characteristics: (1) The negative electrode solid electrolyte includes a garnet-type solid electrolyte; (2) The oxide includes at least one of Al2O3, SnO2, SiO2, TiO2, and ZrO2; (3) The mass ratio of the negative electrode solid electrolyte to the mass of the oxide is (1:4) to (2:3); (4) The negative electrode active material layer includes a negative electrode active material, and the negative electrode active material includes at least one of graphite, silicon oxide material, silicon carbon material, and lithium metal; (5) The thickness of the negative electrode solid electrolyte layer is 5 μm to 15 μm; (6) The thickness of the negative electrode active material layer is 70 μm to 200 μm; (7) The reduction potential of the negative electrode solid electrolyte is lower than the reduction potential of the positive electrode solid electrolyte layer.

10. The method for preparing a lithium battery according to claim 6 or 7, wherein: The method further includes: injecting an electrolyte into the shell, wherein the electrolyte includes a lithium salt; optionally, the lithium salt includes at least one of LiPF6, LiClO4, LiBF4, LiFSI, and LiTFSI.